New Advances in the Kinetic Modeling of Thermal Oxidation of Epoxy-Diamine Networks - Colin, Xavier; Delozanne, Justine; Moreau, Gurvan (Frontiers in Materials, 2021)
This article deals with the thermal oxidation mechanisms and kinetics of epoxy-diamine (EPO-DA) networks used as composite matrices reinforced with carbon fibers in the aeronautical field. The first part of this article is devoted to a detailed presentation of the new analytical kinetic model. The so-called “closed-loop” mechanistic scheme, developed in the last 3 decades in our laboratory in order to accurately describe the thermal oxidation kinetics of saturated hydrocarbon polymers, is recalled. Its main characteristics are also briefly recalled. Then, the system of differential equations derived from this oxidation mechanism is analytically solved without resorting to the usual simplifying assumptions that seriously degrade the reliability of all kinetic models. On the contrary, the generalization of the proportionalities observed between the steady concentrations of the different reactive species (i.e., hydroperoxides and alkyl and peroxy radicals) to the entire course of thermal oxidation gives a series of much sounder equations. From this basis, the kinetic model is completed by considering new structure/property relationships in order to predict the consequences of thermal oxidation on the thermomechanical properties, in particular on the glass transition temperature (Tg). To reach this second objective, the two main mechanisms responsible for the alteration of the macromolecular network structure are recalled: chain scissions and crosslinking. Like any other chemical species, their kinetics are directly expressed from the oxidation mechanistic scheme using the classical concepts of chemical kinetics. The second part of this article is devoted to the checking of the kinetic model reliability. It is shown that this latter accurately simulates the experimental curves of carbonyl build-up and Tg decrease versus time of exposure determined in our laboratory for three EPO-DA networks under study, exposed in a wide variety of thermal oxidative environments. The values determined by inverse solving method for the different model parameters are discussed and their temperature dependence are elucidated. Finally, an end-of-life criterion is proposed for predicting the lifetime of EPO-DA networks involving a predominant chain scission process.